BY STAĆ SIĘ KIMŚ – O KSZTAŁTOWANIU TOŻSAMOŚCI W SZKOLNICTWIE WYŻSZYM - Edström, Eva (Adult Education Discourses, 2010)
The Swedish higher education system is, from an international perspective, described as an open system. As a consequence, higher education is also an arena for non-traditional students. Being the first generation in a family to study in Swedish higher education is one way to define a non-traditional student in this study. Other ways include: male students in an education where women are in the majority, students with working experience, students with ethnical background other than Swedish, and students with disabilities. The aim of this paper is to understand how these non-traditional learners are forming identities within two educational contexts, and how they imagine their future careers and occupational identities in relation to the educational context. The study is based on ten biographical interviews with third-year students of higher education. One group is studying to become physiotherapists and the other one is studying biomedicine. The first group is studying in order to get a particular profession, whereas for the other group education is a way to obtain more general academic degree. These approaches may influence the way the students are forming learning identities and their perception of their future careers and occupational identities. The processes of forming identities are analysed as a relation between structure and agency, and seen as both ‘learning about’ and ‘learning to be’. When studying in higher education to obtain a particular profession, the students are not expected to relate to academy as such but to learn an identity related to their future occupation. When studying for a general academic degree, the students have to develop an academic’s identity. Thus, the two educational contexts in this study are related to academy, though in different ways. The way they relate seems to influence whether the fact of belonging to the first generation in higher education results in clashes.